A The Effect of the Mind Mapping Method on Student Activity and Learning Outcomes in High School Biology - Nadiatul Khairiah; Rahmi Kurniati; Lufri Lufri (Al-Alam: Islamic Science Education Journal, 2026)
Biology education involves numerous interconnected concepts, necessitating teaching methods that help students link information ia a structured manner. This study aims to examine the impact of the mind mapping method on student activity and learning outcomes in biology classes at the senior high school level (SMA/MA) through a literature review. The review analyzed scientific articles published between 2019-2025, sourced from Google Scholar and other academic databases using keywords such as “mind mapping,” “learning outcomes,” “learning activity,” and “biology learning.” The findings indicate that the mind mapping method generally has a positive effect on enhancing student activity and learning outcomes in biology at the senior high school level. Improvements in learning outcomes were evidenced by higher grades and increased mastery of the material. Furthermore, the mind mapping method fosters student engagement in processing information, participating in discussions. Additional research is needed to further explore the simultaneous impact on both of these aspects.